Spirituality as a mediator on the relationship between ethical competency and self-efficacy - Subarimaniam, Neerushah; Zakaria, Noor Syamilah; Wan Jaafar, Wan Marzuki; Wong, Su Luan (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
Codes of ethics polish counseling practices and aspirations. Effective counselors would integrate codes of ethics and the knowledge of laws into their work. The process of incorporating knowledge of law into research is essential due to the nature that every counselor is adhered to legal obligations and concurrently, protected for all their profession liabilities especially in dealing with legal and ethical issues. However, the explicit nature of ethical issues encountered by counselors has not been sufficiently captured, requiring more scrutiny. Thus, the main aim of this conceptual paper is to study the mediating effect of spirituality on the relationship between ethical competency and self-efficacy in dealing with legal and ethical issues. This paper provides discussion about the major components of a research. The research objectives and research questions have been outlined followed by research significance. Next, a number of article journals were used to acquire literature on the topic focusing on the connections between variables. The conceptual framework will allow the readers to understand the link between variables. This research will adopt a quantitative method which involves distribution of survey questionnaires whilst implementing correlational research design. The process of data analysis will involve screening of missing data, exploratory data analysis, descriptive analysis, and structural equation modeling. The predicted findings are presented at the end of the paper.